Following the mechanisms of bacteriostatic versus bactericidal action using Raman spectroscopy - Bernatová, Silvie; Samek, Ota; Pilát, Zdeněk; Serý, Mojmír; Ježek, Jan; Jákl, Petr; Siler, Martin; Krzyžánek, Vladislav; Zemánek, Pavel; Holá, Veronika; Dvořáčková, Milada; Růžička, Filip (Molecules (Basel, Switzerland), 2013)
Antibiotics cure infections by influencing bacterial growth or viability. Antibiotics can be divided to two groups on the basis of their effect on microbial cells through two main mechanisms, which are either bactericidal or bacteriostatic. Bactericidal antibiotics kill the bacteria and bacteriostatic antibiotics suppress the growth of bacteria (keep them in the stationary phase of growth). One of many factors to predict a favorable clinical outcome of the potential action of antimicrobial chemicals may be provided using in vitro bactericidal/bacteriostatic data (e.g., minimum inhibitory concentrations-MICs). Consequently, MICs are used in clinical situations mainly to confirm resistance, and to determine the in vitro activities of new antimicrobials. We report on the combination of data obtained from MICs with information on microorganisms' "fingerprint" (e.g., DNA/RNA, and proteins) provided by Raman spectroscopy. Thus, we could follow mechanisms of the bacteriostatic versus bactericidal action simply by detecting the Raman bands corresponding to DNA. The Raman spectra of Staphylococcus epidermidis treated with clindamycin (a bacteriostatic agent) indeed show little effect on DNA which is in contrast with the action of ciprofloxacin (a bactericidal agent), where the Raman spectra show a decrease in strength of the signal assigned to DNA, suggesting DNA fragmentation.
Keywords: Staphylococcus epidermidis; Spectrum Analysis, Raman; antibakteriální látky; Ramanova spektroskopie; Ciprofloxacin; Microbial Sensitivity Tests; DNA, Bacterial; ciprofloxacin; DNA bakterií; Clindamycin; Anti-Bacterial Agents; klindamycin; mikrobiální testy citlivosti